Pengaruh Kualitas Produk dan Diskon Harga Terhadap Pembelian Implusif Bussana Muslim dengan Minat Beli Sebagai Variabel Intervening - Riski Pangestu; Muhammad Sholahuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the effect of product quality, price discounts on intrusive purchases with purchase intention as intervening. This research uses quantitative methods. The research sample was 150 people who were taken by random sampling. The data analysis techniques used are descriptive statistical tests, model fixity tests, classical assumption tests. coefficient of determination, t-test and path analysis. classical assumption tests used in this study include: normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. Based on the t test results, it shows that product quality, price, partially have a significant positive effect on implusive purchases. Based on the path analysis test, purchase intention is able to mediate the relationship between product quality and price discounts on implusive buying.